Source tracing and health risk assessment of phthalate esters in household tap-water: A case study of the urban area of Quanzhou, Southeast China - Long Wang; Jianyong Li; Jiazuo Zheng; Jing Liang; Rongli Li; Zhenbin Gong (Ecotoxicology and Environmental Safety, 2022)
The occurrence of phthalate esters (PAEs) in household tap water has been investigated via the presence of their geochemical characteristics in the pretreatment and transfer processes of water plants in the urban and suburban areas of the subtropical medium-sized city of Quanzhou, southeast China. The results for all approximately 300 tap water samples collected from 6 sampling stations at household kitchens from Nov. 30, 2017, to Dec. 6, 2018, showed that dimethyl phthalate (DMP), diethyl phthalate (DEP), diisobutylphthaate (DIBP), di-n-butyl phthalate (DBP), and di(2-ethylhexyl) phthalate (DEHP) could be identified and quantified among the 16 PAE congeners with the developed gas chromatographymass spectrometry method. The levels of the sum of 5 PAE congeners (Σ5PAEs) for all tap water ranged from 780.0 ng/L to 9180 ng/L, while DIBP and DEHP were the most abundant congeners, accounting for 82.2% in the dry season, 89.9% in the normal season, and 89.3% in the wet season. Factors of the transferring process, such as the spatial distance from the sampling station to the water plant, the material of pipelines, and the storage time of tap water in the pipeline, affected the levels of PAE congeners in tap water from the correlation of Σ5PAEs levels and transferring distance according to hierarchical cluster analysis. The seasonal variations in Σ5PAEs and each congener had good agreement with the temperature, suggesting that PAEs in tap water mainly come from raw water, which should be further explored in future work. Health risk assessment of PAEs in tap water with the HQ method showed that the occurrence of DEP and DBP has no noncarcinogenic risk for adults and children, while the concentration of DEHP might cause potential noncarcinogenic risk for adults and children, which should be given considerably more attention.